EDUKASI PENERAPAN AKAD KEUANGAN SYARIAH PADA BUMDes Se KECAMATAN TAMBANG - Nurnasrina, Nurnasrina; Khairunisa, Madona; Hasanah, Nur; Syamsurizal, Syamsurizal (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2023)
Tambang District has one of the sharia financial villages, namely Kualu Nenas village, so the BUMDes of this village and other villages need to adapt their BUMDes management based on the sharia financial agreement. This service aims to identify the type of business in each BUMDes, increase the knowledge and understanding of BUMDes managers regarding sharia financial contracts, motivate them to convert to using sharia financial contracts and be able to implement sharia financial contracts in their respective BUMDes. The service method is semi participation action research (semi PAR). The service activity begins by identifying the type of business in BUMDes, providing education and literacy about sharia financial contracts, then asking participants to carry out a simulation of adjusting the appropriate contract for each type of business product in their respective BUMDes. The final stage is that the service team and participants jointly evaluate the results of the simulation whether they are in accordance with the principles of sharia financial contracts or whether they still need to be improved. The results of the service can be seen that, first: the business sectors carried out are savings and loans using a conventional financial system, rental of rice production facilities (saprodi), waserda, mini markets, electronic and motorbike credit, and gas stations. secondly, the level of understanding of BUMdes managers regarding sharia financial contracts has increased but further assistance is still needed over a longer period of time and the majority of participants strongly agree and support the implementation of sharia financial contracts in the BUMDes they manage. Third: the ability of BUMDes managers to apply sharia financial contracts to the products in their respective BUMDes is good but further guidance is still needed. Keywords: BUMDes, sharia financial contract, conversion